(untitled) (International Journal of Food and Nutritional Sciences, 2022)
During the recent COVID-19 outbreak, telemedicine proved to be an invaluable resource. Although the significance of this technology has been previously established and recorded, clinical users have been slow to adopt this digital tool. The drivers of telemedicine adoption, the barriers to its acceptance and use, have been studied by many researchers around the world. Although many such studies focus on technical factors that influence adoption, there are some studies that address user behavioral aspects that influence telemedicine acceptance and use. Studies investigating physician behavior concerning telemedicine adoption are moderately less as compared to patient behavior. Many researchers have attempted to explain the phenomenon using theories drawn from research in psychology and information science. Based on a literature review, we present an evaluation of common behavioral model theories used in telemedicine research.